Kajian Praktik Manajemen Risiko terkait Sustainability pada Divisi Produksi: Studi Kasus pada PT XYZ - Ramadhana, Jethro Muhammad; Sugihartanto, Mushonnifun Faiz (Universitas Muhammadiyah Surakarta, 2023)
Sustainability is one of the things that corporations pay attention. Many parties have deep concerns about future generations makes corporations obliged to take sustainability seriously. One of the things that can be considered by corporations is their production process. Production activities are processes that are carried out by a corporation to transform inputs into outputs. This production process is prone to risks, where the risks in production activities can threaten a corporation on long-term vision or sustainability. So, it is important to carry out risk management about sustainability-related risks in the corporation production process. In this study, the object of the research is PT XYZ, a company that produces educational aid, PT XYZ was founded in 1970 but until now PT XYZ does not know about sustainability-related risks, especially in their production. Therefore, this research will help PT XYZ in conducting risk assessment, and risk analysis, and providing recommendations for risk mitigation with FMEA and cause and effect analysis. The result of the study showed that a risk production budget exceeding was the highest risk with an RPN of 114.59.